The Efficacy of Using Self and Peer-Correction Technique in Teaching Writing Descriptive Text to Indonesian English as Foreign Language (EFL) Students - Taka, Soleman Dapa (Institut Agama Islam Negeri Palopo, 2023)
This research aims at finding out the efficacy of using Self and Peer- Correction Technique in teaching writing especially descriptive text to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of Self and Peer- Correction Technique effective in teaching writing to Indonesian EFL students? The research can be an addition to the persisting teaching writing in English particularly the descriptive text through the use of guided questions. This research was conducted at the tenth-grade students at SMA Kristen Mercusuar Kupang, an Indonesian High School. The total number of samples was 25 students. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in mastering writing descriptive text and the post-test given to find out the students’ improvement in mastering writing descriptive text after giving the treatment by using Self and Peer- Correction Technique. The findings show that using Self and Peer- Correction Technique is effective in teaching writing descriptive text to Indonesian EFL students. It is supported by the result of the significance test through SPSS 20 program that the P was 0.00. Therefore, it is recommended to use the guided questions in developing students’ writing descriptive of Indonesian EFL students.